2012
DOI: 10.1139/x2012-009
|View full text |Cite
|
Sign up to set email alerts
|

Identification of representative sampling heights for specific gravity and moisture content in plantation-grown loblolly pine (Pinus taeda)

Abstract: Conventionally, increment cores collected at breast height (1.4 m) have been used to measure wood properties of standing loblolly pine (Pinus taeda L.) trees. This height has been used because of the ease of sampling and cost involved in extracting the cores. In this study, the efficacy of a breast-height core to represent whole-tree specific gravity (SG) and moisture content (MC) was examined. The sampling height that best represents whole-tree SG and MC was identified using the correlation between volume-wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The stem wood and stem bark densities of each stem disk sample were calculated with dry weight and fresh volume. Based on the relationships between the wood and bark density of stem disks and the locations of the stem disk samples (i.e., the distances of the stem disk from tree top), stem wood and stem bark densities at 1.3 m were identified with tree‐level average density (Antony, Schimleck, & Daniels, ).…”
Section: Methodsmentioning
confidence: 99%
“…The stem wood and stem bark densities of each stem disk sample were calculated with dry weight and fresh volume. Based on the relationships between the wood and bark density of stem disks and the locations of the stem disk samples (i.e., the distances of the stem disk from tree top), stem wood and stem bark densities at 1.3 m were identified with tree‐level average density (Antony, Schimleck, & Daniels, ).…”
Section: Methodsmentioning
confidence: 99%
“…Wet biomass, which includes a variable amount of moisture, can only be determined by field measurements. Some studies found variation in basic density and moisture content from the stump to the top in conifers (Antony et al 2012). Such information is crucial to accurately calculate dry weight biomass and carbon stocks.…”
Section: Introductionmentioning
confidence: 99%